Preliminary Study in Children with Autistic Savant Syndrome - Sah, Vijay Kumar (Journal of Nobel Medical College, 2015)
Background: Savant syndrome, characterized by remarkable islands of mental ability in otherwise mentally handicapped persons, may occur in autistic as well as non autistic individuals. Overall, approximately 10% of autistic persons exhibit savant abilities. Savant skills are typically confined to five areas: art, music, calendar calculating, mathematics and mechanical/spatial skills. Methods: Data taken from the third affiliated hospital of Sun Yat- Sen university from December 09, 2008 to September 08, 2009. We have analyzed 885 cases, among them 725 were with autistic disorder and 160 were of Mental retardation. Total subjects enrolled were altogether 48; Male 45, Female 3 with mean and SD of age 7.08 ± 2.31 years. Number of savant skills in children group includes 11 Autism, 10 HFA, 26 AS, 1 MR. Results: Approximately one in thirteen (7%) of children with autistic disorder had savant skills in our study. Approximately less than 1% of children with developmental disability, mental retardation had savant skills in our study. Overall, many more males showed some form of savant skill. Artistic skill is one of the most common savant skills seen in autistic children. The socioeconomic status of the parents of autistic children was relatively high. Conclusions: We thus conclude that autism (or autistic traits) and savant skills are inextricably linked and we should therefore look to autism in our quest to solve the puzzle of the savant syndrome. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12232 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 20-25